Predictors of Symptoms Remission Among Family Caregivers of Individuals With Dementia Receiving REACH VA. Issue 6 (September 2019) - Chen, Cory K.; Nehrig, Nicole; Abraham, Karen S.; Wang, Binhuan; Palfrey, Amy P.; Baer, Alyssa L.
Resources for Enhancing All Caregivers Health (REACH VA) is a behavioral intervention for caregivers of individuals with dementia disseminated in the VA. Although shown to improve caregiver and care recipient outcomes, some caregivers continue to experience depression or caregiver burden following the intervention. Factors that predict symptom remission following REACH VA are unknown. The present study investigated attachment, social support, and psychopathology as predictors of symptom remission for family caregivers who completed REACH VA. Caregivers who do not remit perceive lower levels of social support from loved ones, endorse poorer attachment quality, and have more personality disorder characteristics, particularly affective instability. These factors that impair caregivers' abilities to be effectively attuned to the needs of their care recipients and to reap benefits from a brief and focused behavioral intervention such as REACH VA. Interventions that target caregiver interpersonal functioning and emotion regulation skills may be helpful to those who do not respond to REACH VA.